Transnational Organized Crime and the UN Convention - Akkoyun, Aişe Gül; Çelik, Muhammet Emir (Frontiers in Law, 2023)
The United Nations Convention against Transnational Organized Crime, as well as regional, national, and international collaboration to prevent and control transnational organized crime, are discussed in this paper. It investigates the transnational organized crime implementation mechanism and jurisdiction in light of international criminal law and the crimes and elements covered by the Convention. The paper recognizes that, as the importance of international criminal law in combating transnational organized crime grows, the ICC’s approach to bringing transnational organized crime under its jurisdiction is gained importance. The main conclusion is that implementing the Convention’s prevention and protection mechanism for transnational organized crime has been difficult; hence the ICC’s jurisdiction would have an impact on the ground.